1992
DOI: 10.1002/mrd.1080310308
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of bovine oocyte maturation in vitro

Abstract: Bovine cumulus-oocyte complexes (COCs) were collected from 4-8 mm follicles and graded into four categories on their morphological characteristics. These four categories were matured in vitro and processed for transmission electron microscopy at 24 h after the onset of culture. The morphology of the four groups of oocytes was analysed and compared with that of oocytes that had matured in vivo and were collected 20-23 h after the preovulatory luteinizing hormone peak. After in vivo maturation, oocytes formed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 24 publications
5
42
0
2
Order By: Relevance
“…The present results agreed with previous findings [4,5] that oocytes having heterogeneous ooplasm with dark clusters have potential for nuclear maturation in vitro comparable to that of oocytes with homogeneous ooplasm. However, the maturation rate of oocytes with heterogeneous ooplasm after 24-hr culture was reported to be significantly higher than that of oocytes with homogeneous ooplasm [12].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results agreed with previous findings [4,5] that oocytes having heterogeneous ooplasm with dark clusters have potential for nuclear maturation in vitro comparable to that of oocytes with homogeneous ooplasm. However, the maturation rate of oocytes with heterogeneous ooplasm after 24-hr culture was reported to be significantly higher than that of oocytes with homogeneous ooplasm [12].…”
Section: Discussionsupporting
confidence: 93%
“…It was shown that the difference in the cortical granule distribution was present in the oocytes with various morphologies before in vitro maturation [5], and was no longer observed after in vitro maturation [4]. However, the difference in the cortical granule distribution in each Values are means ± SD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cumulus expansion is usually more extensive following maturation in vivo [75]. In addition, there is a high degree of homogeneity amongst oocytes matured in vivo at the ultrastructural level; this contrasts with the ultrastructural heterogeneity exhibited by in vitro matured oocytes, even when a uniform population of the latter is selected prior to in vitro maturation [17].…”
Section: Differences Between In Vivo-and In Vitro-produced Embryosmentioning
confidence: 98%